Congenital right bronchial stenosis with high bifurcation: Successful management with side to side tracheobronchial anastomosis. (August 2018) - Georgopoulos, Rachel; Hill, Courtney; Heinle, Jeffrey S.; Mehta, Deepak
Abstract: Congenital bronchial stenosis is a rare entity [1, 2]. While there are some reports of congenital bronchial anomalies and their repair in the thoracic literature this is first report in the literature of a bronchial take off just below the larynx managed with surgical success. Here we present a case of a former 33-weeker born with a tracheoesophageal fistula, Tetralogy of Fallot, and a high bifurcation of the right mainstem bronchus with a concomitant long segment bronchial stenosis. Preoperative planning included printing 3-D reconstructed models of the airway to analyze various treatment options. At 3 months of age the patient was taken to the operating room for surgical repair of the Tetralogy of Fallot and side-to-side tracheobroncheoplasty. The patient was extubated on postoperative day 3 and was discharged home without need for any ventilatory support.